The Numerical Investigation of the Heat Transport in the Nanofluids under the Impacts of Magnetic Field: Applications in Industrial Zone. (28th July 2021) - Adnan,; Khan, Umar; Ahmed, Naveed; Mohyud-Din, Syed Tauseef; Khan, Ilyas; Fayz-Al-Asad, Md.
Abstract : The dynamics of the nanofluid flow between two plates that are placed parallel to each other is of huge interest due to its numerous applications in different industries. Keeping in view the significance of such flow, investigation of the heat transfer in the Cu-H2 O nanofluid is conducted between parallel rotating plates. For more significant results of the study, the squeezing effects are incorporated over the plates that are electrically conducting. The nondimensional flow model is then treated analytically (VPM), and the results are sketched against the preeminent flow parameters. The remarkable heat transfer in the nanofluid is noticed against the Eckert and Prandtl numbers, whereas the Lorentz forces oppose the fluid temperature. Furthermore, the shear stresses at the walls drop and the local heat transfer rate rises due to increasing flow parameters. Finally, to validate the study, a comparison is made with existing available science literature and noted that the presented results are aligned with them.